An assessment of power flexibility from commercial building cooling systems in the United States. (15th April 2021) - Huang, Sen; Ye, Yunyang; Wu, Di; Zuo, Wangda
Abstract: Understanding the varying characteristics and aggregate potential of power flexibility from different building types considering regional diversity is critically important to actively engaging building resources in future eco-friendly, low-cost, and sustainable power systems. This paper presents a comprehensive characteristics analysis and potential assessment of the power flexibility from heating, ventilation, and air conditioning loads in commercial buildings in the U.S. using a simulation-based method. Commercial buildings are first grouped by building type and climate region. The U.S. Department of Energy Commercial Prototype Building Models are used to represent an average building in each group and are simulated to characterize power flexibility. Based on building survey data, the number of commercial buildings in each group is estimated and used to calculate aggregate power flexibility. It is found that cooling loads in commercial buildings offer more flexibility for increasing power consumption than for decreasing it. The power consumption of commercial buildings in the U.S. can be increased by 46 GW and decreased by 40 GW on peak summer days. Among all commercial building types, standalone retail buildings provide the most absolute flexibility while medium office buildings have the most flexibility as a percentage of the rated power consumption. Highlights: A simulation-based method is proposed to assess flexibility of commercial buildings. High-fidelity building models in EnergyPlus™ are employed. Key factors that affect commercial building power flexibility are identified and analyzed. Aggregate flexibility is estimated by building type and by region for the entire U.S.